THE EFFECT OF INTERACTION QUALITY, PERCEIVED PERFORMANCE EXCELLENT AND RELATIONSHIP SATISFACTION ON CONSUMER TRUST AND LOYALTY (Case Study: Rattan Craft Business "UD. Rattan Handmade" Pekanbaru): PENGARUH KUALITAS INTERAKSI, KINERJA YANG DIRASAKAN DAN HUBUNGAN KEPUASAN TERHADAP KEPERCAYAAN DAN LOYALITAS KONSUMEN (Studi Kasus: Usaha Kerajinan Rattan “UD. Rattan Handmade” Pekanbaru) - Syaiful Hadi; Fajar Restuhadi; Devinda Desi Indra Murti (Jurnal Agribisnis, 2023)
ABSTRACT This study aims to analyze the effect of Interaction Quality UD. "Rattan Handmade" on consumer trust. Analyzing the effect of Interaction Quality UD. "Rattan Handmade" on consumer loyalty, analyzing the effect of Perceived Performance Excellence UD. "Rattan Handmade" on consumer trust, analyzing the effect of Perceived Performance Excellence UD. "Rattan Handmade" on consumer loyalty, analyzing the effect of Relationship Satisfaction UD. "Rattan Handmade" on consumer trust, analyzing the effect of Relationship Satisfaction UD. "Rattan Handmade" on consumer loyalty, analyzing the effect of trust on consumer loyalty. This study uses the SEM-AMOS analysis method and is assisted by using AMOS 22 software. The results of this study are that there is a positive influence of Interaction Quality on consumer trust according to the estimation results of the standardized regression weight coefficient obtained at 0.263 and a CR value of 2.492. There is a positive effect of Perceived Performance Excellent on Trust, according to the estimation results of the standardized regression weight coefficient obtained at 0.318 and the CR value of 2.319. There is a positive influence of Relationship Satisfaction on Trust. According to the estimation results, the coefficient value of the standardized regression weight was 0.385 and the CR value was 2.960. There is a positive influence of Interaction Quality on Loyalty. According to the estimation results, the coefficient value of the standardized regression weight was 0.296 and the CR value was 2.780. There is a positive effect of Perceived Performance Excellent on Loyalty, according to the estimated results of the standardized regression weight coefficient value obtained at 0.348 and a CR value of 2. There is no positive effect of Relationship Satisfaction on Loyalty, according to the estimation results the standardized regression weight coefficient value is obtained at 0.195 and a CR value of 1,481. There is a positive influence of Trust on Loyalty. The results of the hypothesis test showed that the estimated parameter coefficient value of the standardized regression weight was 0.342 and the CR value was 2.152. Keywords: Interaction Quality, Loyalty ,Perceived Performance Excellent, Relationship Satisfaction, Trust